2014
DOI: 10.1073/pnas.1407466112
|View full text |Cite
|
Sign up to set email alerts
|

Activated CD4 + CCR5 + T cells in the rectum predict increased SIV acquisition in SIVGag/Tat-vaccinated rhesus macaques

Abstract: An effective T-cell–based AIDS vaccine should induce strong HIV-specific CD8+ T cells in mucosal tissues without increasing the availability of target cells for the virus. Here, we evaluated five immunization strategies that include Human adenovirus-5 (AdHu5), Chimpanzee adenovirus-6 (AdC6) or -7 (AdC7), Vaccinia virus (VV), and DNA given by electroporation (DNA/EP), all expressing Simian immunodeficiency virus group specific antigen/transactivator of transcription (SIVmac239Gag/Tat). Five groups of six rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…Indeed, the shared chemotactic activities of these neutrophil granule-derived proteins could be the driving force behind the immune cell recruitment and the corresponding epithelial barrier disruption observed during the luteal phase in the present study, which may contribute to the overall vulnerability to HIV infection observed during this time. It is possible that the HIV target cell populations and/or phenotypes, which can impact HIV acquisition risk due to an increased expression of HIV coreceptors (54), varied at the mucosal surface of these luteal-phase samples; however, we were unable to confirm this in our study since matching cytobrush and/or biopsy samples were not collected for this purpose. A longitudinal study assessing these immune cell populations in parallel with these molecular signatures would help answer this question.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, the shared chemotactic activities of these neutrophil granule-derived proteins could be the driving force behind the immune cell recruitment and the corresponding epithelial barrier disruption observed during the luteal phase in the present study, which may contribute to the overall vulnerability to HIV infection observed during this time. It is possible that the HIV target cell populations and/or phenotypes, which can impact HIV acquisition risk due to an increased expression of HIV coreceptors (54), varied at the mucosal surface of these luteal-phase samples; however, we were unable to confirm this in our study since matching cytobrush and/or biopsy samples were not collected for this purpose. A longitudinal study assessing these immune cell populations in parallel with these molecular signatures would help answer this question.…”
Section: Discussionmentioning
confidence: 75%
“…One study showed that PBMC IFN-␥ enzyme-linked immunosorbent spot assay (ELISPOT) responses inversely correlated with the number of SIV exposures needed to establish infection in adult macaques (72). Another study comparing various vaccine modalities showed that regardless of the vaccine strategy, the number of activated CD4 ϩ T cells in the rectal mucosa predicted early viremia and risk for rectal SIV infection (73). Both studies established a link between immune activation at the time of challenge and SIV exposure risk, although a statistically significant difference in challenge outcome between the groups was not demonstrated (72,73).…”
Section: Trained Immunity and Immune Activation Of Tb Vaccinesmentioning
confidence: 99%
“…Another study comparing various vaccine modalities showed that regardless of the vaccine strategy, the number of activated CD4 ϩ T cells in the rectal mucosa predicted early viremia and risk for rectal SIV infection (73). Both studies established a link between immune activation at the time of challenge and SIV exposure risk, although a statistically significant difference in challenge outcome between the groups was not demonstrated (72,73). Similarly, in a recent low-dose rectal SIV infection study, animals with higher numbers of Ki67-positive CD4 ϩ T cells in the colorectal mucosa required fewer SIV exposures to become infected (74).…”
Section: Trained Immunity and Immune Activation Of Tb Vaccinesmentioning
confidence: 99%
“…[26][27][28][29][30][31] In this study, we aim to characterise mucosal immunity before and after vaccination with a commercial live-attenuated VZV vaccine with respect to immune activation state, mucosal homing properties and VZV-specific effector immune responses in Kenyan women at low risk for HIV acquisition and with preimmunity to VZV through natural infection. Characterising VZV responses in this study setting is highly relevant, since Kenya, along with other African countries, is among the countries which can derive the greatest benefit with an HIV vaccine.…”
Section: Open Accessmentioning
confidence: 99%